Common Mistakes in Writing Citation Found on English Students Literature Review Thesis in English Education Program of Muhammadiyah University of Bengkulu - Mega Rahmadania; Epi Wadison (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The primary purpose of this research is describe about common mistakes in writing citation found on English Students’ Literature Review Thesis in English Education Program of Muhammadiyah University of Bengkulu. The research design of this research used qualitative method. The instrument is using table cheklist about mistakes in writing citation by APA Style 7th edition : Direct Citation and Indirect Citation. The result of this study showed that there were common mistakes in writing citation found on English Students’ Literature Review Thesis. First, Directcitation in book sources, most of English Students did not write page number as initial “p”. Second, indirect citation from the book sources, most of the students did not write “as cite in” as characteristics in writing Indirect Citation. Third, Direct Citation from journals sources, most of English Students write Paragraph number using colon, not use initial “para” as in APA guiding style. Fourth, Indirect Citation from the journals sources, most of the English Students did not write words “as cite in” as a characteristics in writing indirect citation. Fifth, the common mistakes in writing Indirect Citation in English Students Literature Review Thesis from Book sources in single author, especially in writing page number. On the other hand, the common mistakes in writing Indirect Citation in English Students Literature Review from the book sources in single author especially in write the words “as cite in”. The common mistakes in writing direct citation from the journals sources in single author in writing paragraph number, and the common mistakes in writing indirect citation from the journals sources in single author especially in write the words “as cite in”. Key words: Citation, literature review, academic writing